Factors Influencing Capital Structure and Its Impact Toward Profitability in Consumer Goods Manufacturing Companies Listed in the IDX for the 2019-2023 Period - Rosita, Hani; Nuryaman, Nuryaman (DINASTI RESEARCH, 2025)
This research aims to analyze the influence of non-debt tax shield (NDTS), business risk, and company size on capital structure and its impact on profitability. The research adopts a quantitative method with a sample of 46 manufacturing companies in the consumer goods sector. The analysis was conducted using multiple regression analysis processed with SPSS. The results reveal that NDTS has a significant negative effect on capital structure. Tax savings from depreciation replace the tax benefits of interest, leading companies with high NDTS to reduce debt usage. Business risk also has a significant negative effect on capital structure. Companies with high business risk prefer a conservative capital structure, relying on equity or internal funds to mitigate default risk. Conversely, company size has a significant positive effect on capital structure. Capital structure significantly negatively affects profitability. While debt can enhance profitability if managed properly, a high debt proportion increases interest burdens, thereby reducing profits.